2019
DOI: 10.1177/1753193419893890
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of scapholunate instability with dynamic computed tomography

Abstract: We performed a prospective study to evaluate the values of dynamic four-dimensional computed tomography in assessing suspected chronic scapholunate instability. Forty patients were evaluated with radiographs, arthrography, and four-dimensional computed tomography. On plain radiographs and computed tomography, we found 16 patients with definite scapholunate instability, five with questionable scapholunate instability, and 19 with absence of scapholunate instability. We used four-dimensional computed tomography … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 15 publications
0
17
0
1
Order By: Relevance
“…Kinematic-CT can diagnose SLJ instability, especially when the conventional diagnostic evaluation is inconclusive [35][36][37][38]. It has been suggested that kinematic-MRI is a fast and reliable technique for detecting dynamic SLJ instability with a diagnostic accuracy comparable to dynamic fluoroscopy [39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…Kinematic-CT can diagnose SLJ instability, especially when the conventional diagnostic evaluation is inconclusive [35][36][37][38]. It has been suggested that kinematic-MRI is a fast and reliable technique for detecting dynamic SLJ instability with a diagnostic accuracy comparable to dynamic fluoroscopy [39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…[47][48][49] Four-dimensional CT achievable with devices with large detection system could play a role in the analysis of normal and pathologic kinematics of different joints. [50][51][52][53] CT angiography can be useful to evaluate vascular lesions and rule out a tumor 54,55 (►Fig. 7).…”
Section: Computed Tomographymentioning
confidence: 99%
“…In addition, the greater the variation in the scapholunate gap, the less stable the scapholunate joint, and the increased likelihood that the wrist would progress to scapholunate instability. Conversely, radiographic scapholunate diastasis that remains stable or exhibit minimal variations during wrist movements is not usually associated with a degree of instability that would progress to arthritis (Athlani et al., 2020). Thus, it should be possible to detect earlier stages of predynamic instability and treat these conservatively, while limiting the number of unnecessary repairs in stable lesions that have little risk of developing arthritis.…”
Section: Existing Challenges and The Futurementioning
confidence: 99%